The Ring 0 : birthday - Suzuki, Koji; Takahashi, Hiroshi; Meimu; Kokubo, Naomi; Hoffman, Steven; Lacuna, Wilbert (Milwaukie, OR : Dark Horse Manga, 2000)
Final installment in the Ring manga adaptation, depicting the terrifying events surrounding cursed videotapes and supernatural phenomena.
English translation of the Japanese manga.
Keywords: Horror fiction; Manga; Japanese literature $v Comic books, strips, etc